Immune Deviation in the Decidua During Term and Preterm Labor - Zha, Ying; Liu, Haiyi; Lin, Xingguang; Yu, Long; Gao, Peng; Li, Yuqi; Wu, Min; Gong, Xun; Bian, Xinyi; Kang, Qi; Zhi, Pan; Dang, Xiaohe; et al. (Frontiers in Immunology, 2022)
The maternal-fetal immune disorder is considered to be an important factor of preterm birth (PTB); however, the underlying mechanism is still not fully understood. This study was designed to explore the innate and adaptive immune features in the decidua during term and preterm labor. Women delivered at term or preterm were classified into four groups: term not in labor (TNL, N=19), term in labor (TL, N=17), preterm not in labor (PNL, N=10), and preterm in labor (PIL, N=10). Decidua basalis and parietalis were collected and analyzed for macrophage subtypes (M1 and M2) as well as T helper 1 (Th1), Th2, Th17 and regulatory T (Treg) cells by flow cytometry and immunohistochemistry. Our results demonstrated significantly decreased frequencies of M2 cells and elevated M1/M2 ratio in the PIL group compared to that in the PNL group in both decidua basalis and parietalis, whereas no significant differences were found between the above two groups in both sites in terms of the polarization status of Th cells. On the contrary, macrophage subsets were comparable in the TL and TNL groups, whereas elevated Th1 percentages and Th1/Th2 ratio were observed in TL women compared to that in TNL women in the decidua. Interestingly, although the frequencies and ratios of Th17 and Treg were comparable among the four groups, the Th17/Treg ratios of these groups were significantly increased in decidua basalis than that in decidua parietalis. Collectively, the M1/M2 imbalance is associated with the breakdown of maternal-fetal immune tolerance during PTB, whereas the aberrant Th1/Th2 profile plays an important role in immune disorder during term labor. Moreover, Th17/Treg deviation is more remarkable in decidua basalis than in decidua parietalis.